ANALYSIS OF INTELLECTUAL PROPERTY RIGHTS REGULATIONS IN THE INFORMATION TECHNOLOGY LAW: PERSONAL DATA PROTECTION CASE STUDY - syafitri, shinta; Fitria, Yanti; Darmansyah, Darmansyah (Jurnal Tunas Pendidikan, 2025)
Intellectual Property Rights (IPR) and information technology are two things that are closely related. In the current digital era, IPR is becoming increasingly important because of the easy dissemination of information and creative works via the internet. However, this opens up opportunities for IPR violations such as the distribution of personal data and information. For this reason, this research aims to find out how personal data is legally protected for intellectual property rights owners based on the Information Technology Law. This research includes normative legal research where the subject matter or purpose of this research is regulations, legislation and other legal materials. In Indonesia, Article 25 of the ITE Law provides the legal basis for dealing with intellectual property violations related to electronic transactions. This provides a legal basis for intellectual property rights owners to take action against violations of electronic transactions. Article 25 of the ITE Law regulates the protection of intellectual property rights, including copyrights, patents, trademarks and others in electronic transactions. However, the act of misuse of personal data on social media is not related to the personal data of the copyright owner. Therefore, it is important to develop a balanced intellectual property rights policy regarding personal data and harmonize legal regulations to avoid duplication between different regulations. Protection of personal data of intellectual property rights owners, especially in the digital realm which continues to develop.